Desempenho cognitivo, ansiedade e comportamento da pressão arterial em residentes de clínica médica em plantão noturno - Suozzo, Aida Cristina [UNIFESP] (2011)
Introduction: The consequences of the stress of medical activities are making research and concerns. Night shift, workload, fatigue, exhaustion, fear of making mistakes and lack of supervision have been associated with stress during residency. Objective: This study aimed to assess cognitive performance, anxiety level and blood pressure behavior in a group of first-year residents in internal medicine on the night on-call, after routine activities in stage of wards. Methods: We invited all (n = 40) residents at first-year of internal medicine at ISCMSP. Thirty-eight residents agreed to participate at this cross sectional study. The residents were assessed twice at the same order: the first evaluation-(Stage 1) on a regular routine workday followed by nighttime on-call duty in an emergency room and second evaluation-(stage 2), on a regular routine workday followed by nighttime off duty. Digit Span, Span Spatial, Trail Making Test, Stroop Color Test, Rey Audictory Verbal Learning Test, Wisconsin Card Sorting Test were the neuropsychological tests used for cognitive assessments after the end of two stages. The STAI-state was assessed at beginning and end of night on-call. The blood pressure monitoring was performed by ABPM during 24 h at stage 1 and 2. For data analysis we used: Student’s paired test, Wilcoxon, McNemar, Effect-size (Cohens’d). Differences were considered significant when p < 0.05. Results: After a night on call, the performance of the residents was worse on: Trail Making Test Part A (p=0,016), attention, RAVLT-Trial 1 (p=0,028) in immediate recall, RAVLT-Trial 7 (p =0,016), recognition; RAVLT List B (p=0,006) distracter word list; RAVLT-total (trials 1 to 5) (p=0,035), verbal learning and memory, Stroop Color Test W (p=0,029) inhibitory control of impulse and WCST-perseverative errors (p=0,028), cognitive flexibility. There were no differences between levels of anxiety at the beginning and end of night on-call (p=0,850), 40,71 ( 8.5) and 40,42 (8.3). The mean systolic and diastolic pressures were statistical significant during the daytime (118 v 115 mmHg, p=0.01, 75 v 71 mmHg, p=0,01) and nighttime (116 v 108 mmHg, p < 0,001, 74 v 64 mmHg, p < 0,001) in stage 1 than stage 2. Only at Stage 2 there was difference between daytime and nighttime at blood pressure systolic (115 v 108 mmHg, p < 0,001) and diastolic (71 v 64 mmHg, p < 0,001). 76% of residents did not presented nocturnal fall at Stage 1. Conclusion: The night on-call changed the cognitive performance and behavior of blood pressure medicine residents. Preventive actions in educational institutions should be planned.